2015
DOI: 10.1111/bjet.12311
|View full text |Cite
|
Sign up to set email alerts
|

Research and trends in mobile learning from 1976 to 2013: A content analysis of patents in selected databases

Abstract: Mobile learning has been a very popular topic in the past several decades. As more patents in this field have been submitted, the analysis of patents has surfaced as an important mechanism to understand trends, uses, targeted audiences and other aspects in the mobile learning space. Based on the CNIPR, USPTO, and Espacenet databases, this paper provides an analysis of mobile learning from 1976, when the first patent in mobile learning emerged, to 2013. One hundred thirty patents were analyzed from two dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Educational practices with mobile learning and game-based learning show positive effects on students' learning achievements, motivation for learning in school and interest in the subject matter that they learn in school (Abdul Jabbar & Felicia, 2015;Furió, Juan, Seguí, & Vivó, 2015;So & Seo, 2018;Sung, Chang, & Liu, 2016;Wilson et al, 2009;Wouters, Van Nimwegen, Van Oostendorp, & Van der Spek, 2013). Mobile learning in schools is mostly applied in environmental education or out-of-class schooling (Chiang et al, 2015). This type of learning with mobile devices with wireless network connections, cameras, RFID readers and GPS (Jeng, Wu, Haung, Tan, & Yang, 2010) expands learning with games from the screen to learning in a mixedreality environment using urban spaces as a game board.…”
Section: Introductionmentioning
confidence: 99%
“…Educational practices with mobile learning and game-based learning show positive effects on students' learning achievements, motivation for learning in school and interest in the subject matter that they learn in school (Abdul Jabbar & Felicia, 2015;Furió, Juan, Seguí, & Vivó, 2015;So & Seo, 2018;Sung, Chang, & Liu, 2016;Wilson et al, 2009;Wouters, Van Nimwegen, Van Oostendorp, & Van der Spek, 2013). Mobile learning in schools is mostly applied in environmental education or out-of-class schooling (Chiang et al, 2015). This type of learning with mobile devices with wireless network connections, cameras, RFID readers and GPS (Jeng, Wu, Haung, Tan, & Yang, 2010) expands learning with games from the screen to learning in a mixedreality environment using urban spaces as a game board.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sung et al (2016b) examined 110 experimental journal articles published from 1993 to 2013, and reported that, the use of mobile devices, such as tablet computers, PDAs (Personal Digital Assistants) and smartphones, had great potential in improving students' learning performances if effective learning approaches could be adopted. In the meantime, Chiang et al (2016) investigated the patents of mobile learning between 1976 and 2013, analysing the patents from China Intellectual Property Right Net (CNIPR), the United States Patent and Trademark Office (USPTO) and Espacenet, which included nearly 90 countries.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile learning (or m-learning) has been one of the key current trends of educational applications for new technologies (Wu et al 2012;Camilleri and Camilleri 2017;Chiang et al 2016). It has been described as 'the process of learning mediated by a mobile device' (Kearney et al 2012, p. 2), enabling students to engage in tasks without being 'tightly delimited' to a physical location (Kukulska-Hulme 2005).…”
Section: Mobile Learning and The Use Of Tabletsmentioning
confidence: 99%